THE IMPLEMENTATION OF CORRECTIVE FEEDBACK IN WRITING CLASS FOR THE FIRST YEAR STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM - Qirani, Restu Aulia; Baa, Sultan; Sofyan, Ryan Rayhana (Universitas Negeri Makassar, 2024)
This study aimed to explore the use of corrective feedback in writing classes for first-year students in the English Education Study Program at Universitas Negeri Makassar. Adopting a descriptive qualitative approach, the research involved first-year students as participants, with data collected through observations and interviews. The results showed that the implementation of corrective feedback was effective and positively influenced the writing classes, with participants sharing favorable opinions. The findings indicated that students had a positive perception of their lecturer’s corrective feedback in the writing class.